Pengaruh Fibronektin pada Kultur Sel Punca Limbal (SPL) Tikus - Rinendyaputri, Ratih; Dany, Frans; rifati, Lutfah (Jurnal Biotek Medisiana Indonesia, 2016)
Abstract Availability of limbus stem cells (LSC) is very limited considering the number of donors SCL very less as compared to the needs, so it is necessary LSC production in vitro. The success of in vitro culture of LSC is strongly influenced by environmental conditions, one of which is the use of the extracellular matrix. Selection of the appropriate type of matrix in the LSC culture, can increase proliferation and facilitate the application of transplantation. This study aimed to get activities fibronectin (FN) as extracellular matrix to produce LSC. Research conducted at the Center for Biomedical and Basic Technology of Health. In this study, production of SPL rats performed in vitro using the method of explants on a petri dish with FN as the extracellular matrix. SPL proliferation rate that with and without FN analyzed by calculating the population doublings (PD), PD/day and the population doubling time (PDT). SPL characterization was performed by quantifiying RNA of CD90 gene, p63, ABCG2 and Krt12 as a marker SPL. The results showed that the PD,PD/day PDT in the SPL with and without FN respectively are 2.13 and 2.11, 0.44 and 0.42 , 57.65 and 61.46 (p> 0.05). While the RNA quntitative of CD90Â  , p63, ABCG2 and Krt12 SPL on with and without of FN respectively are 17.70 and 19.75, 17.08 and 18.42, 15.23 and 19.09, 17.42 and 18.85 (p> 0.05). This shows that the FN isnât effective as an extracellular matrix in in vitro cultureSPL.Abstract Â Â Â Â Â  Availability of limbus stem cells (LSC) is very limited considering the number of donors SCL very less as compared to the needs, so it is necessary LSC production in vitro. The success of in vitro culture of LSC is strongly influenced by environmental conditions, one of which is the use of the extracellular matrix. Selection of the appropriate type of matrix in the LSC culture, can increase proliferation and facilitate the application of transplantation. This study aimed to get activities fibronectin (FN) as extracellular matrix to produce LSC. Research conducted at the Center for Biomedical and Basic Technology of Health. In this study, production of SPL rats performed in vitro using the method of explants on a petri dish with FN as the extracellular matrix. SPL proliferation rate that with and without FN analyzed by calculating the population doublings (PD), PD/day and the population doubling time (PDT). SPL characterization was performed by quantifiying RNA of CD90 gene, p63, ABCG2 and Krt12 as a marker SPL. The results showed that the PD,PD/day PDT in the SPL with and without FN respectively are 2.13 and 2.11, 0.44 and 0.42 , 57.65 and 61.46 (p> 0.05). While the RNA quntitative of CD90Â  , p63, ABCG2 and Krt12 SPL on with and without of FN respectively are 17.70 and 19.75, 17.08 and 18.42, 15.23 and 19.09, 17.42 and 18.85 (p> 0.05). This shows that the FN isnât effective as an extracellular matrix in in vitro cultureSPL.